2016
DOI: 10.1113/jp272591
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic receptor activation contrasts pathophysiological bursting and neurodegeneration evoked by glutamate uptake block on rat hypoglossal motoneurons

Abstract: Excitotoxicity is thought to be one of the early processes in the onset of amyotrophic lateral sclerosis (ALS) because high levels of glutamate have been detected in the cerebrospinal fluid of such patients due to dysfunctional uptake of this transmitter that gradually damages brainstem and spinal motoneurons. To explore potential mechanisms to arrest ALS onset, we used an established in vitro model of rat brainstem slice preparation in which excitotoxicity is induced by the glutamate uptake blocker dl-threo-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 127 publications
(185 reference statements)
1
32
0
Order By: Relevance
“…As mitochondrial dysfunction and motoneuron death are observed after 4-h treatment with TBOA, 13 we evaluated Cx36 expression (Figures 3a and b; red) in relation to immunoreactivity of single HMs (identified with SMI 32 immunostaining; green). DAPI was used for nuclear staining (blue).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mitochondrial dysfunction and motoneuron death are observed after 4-h treatment with TBOA, 13 we evaluated Cx36 expression (Figures 3a and b; red) in relation to immunoreactivity of single HMs (identified with SMI 32 immunostaining; green). DAPI was used for nuclear staining (blue).…”
Section: Resultsmentioning
confidence: 99%
“…Even if the nucleus hypoglossus represents only a minor region of this tissue, this approach was earlier useful to detect changes in gene profiling, protein synthesis and expression, and mitochondrial energy production 13, 14 which, although cannot be directly attributed to HMs (or other brainstem motoneurons), yet they provide an index of the metabolic state of the network and of any ongoing neuroprotective process.…”
Section: Resultsmentioning
confidence: 99%
“…Studies performed on hypoglossal motor neurons revealed that muscarinic ACh receptors not only inhibit glutamatergic transmission but also depress inhibitory neurotransmission on brainstem motor neurons . Nevertheless, it was shown that brainstem hypoglossal motor neuron excitotoxicity was suppressed by activation of neuronal nicotinic receptors with their conventional agonist, nicotine . Gamma aminobutyric acid (GABA) activity also modifies the cholinergic system at various levels of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…43 Nevertheless, it was shown that brainstem hypoglossal motor neuron excitotoxicity was suppressed by activation of neuronal nicotinic receptors with their conventional agonist, nicotine. 44 Gamma aminobutyric acid (GABA) activity also modifies the cholinergic system at various levels of the central nervous system. Giorgetti et al reported that, although the GABA-a agonist muscimol has no effect on cortical ACh release, the GABA-b agonist baclofen augments spontaneous ACh release in the rat cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine has shown anti-excitotoxic effects through a calcium-dependent pathway that is mediated via α 7 nAChRs (Shimohama et al, 1998;Dajas-Bailador et al, 2000;Corsini et al, 2016). This may result from the modulatory effects of α 7 nAChRs on the glutamate-induced prevention of the PI3-K/Akt pathway (Cui et al, 2013).…”
Section: Excitotoxicitymentioning
confidence: 99%